2006
DOI: 10.1080/10641950600913016
|View full text |Cite
|
Sign up to set email alerts
|

Lower Rate of Preeclampsia After Antioxidant Supplementation in Pregnant Women with Low Antioxidant Status

Abstract: Antioxidant supplementation was associated with better maternal and perinatal outcome in pregnant women with low antioxidant status than control supplementation with iron and folate alone. In a selected population already screened positive for low SOD, preeclampsia can be detected in 33% of asymptomatic cases in the first trimester using SOD, GPx, and TAS. It seems feasible that panels of both biochemical and molecular markers may be clinically useful in the prediction of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 28 publications
3
65
0
4
Order By: Relevance
“…This enzyme is considered one of the most important antioxidant defense mechanisms and its lower activity was used for screening for low antioxidant status and was even predictive of PEE development [54]. So our result in the PE group is in concordance with previous researches and is a no surprise.…”
Section: International Journal Ofsupporting
confidence: 91%
“…This enzyme is considered one of the most important antioxidant defense mechanisms and its lower activity was used for screening for low antioxidant status and was even predictive of PEE development [54]. So our result in the PE group is in concordance with previous researches and is a no surprise.…”
Section: International Journal Ofsupporting
confidence: 91%
“…The selenium supplemented group had a reduced incidence of development of PIH 473 (7.7%; 4/52) compared to the placebo group (22.7%; 11/48), and significantly increased 474 maternal and cord blood selenium concentrations. Another very small prospective 475 double-blind, placebo-controlled RCT study in Indonesia, reported lower rates of pre-476 eclampsia and/or PIH in women who were at increased risk of developing these 477 conditions, after supplementation (n = 29) with a range of antioxidants and cofactors 478 including selenium (100 μg) (Rumiris et al, 2006). Neither study adequately addressed 479 the role of supplementation on the incidence of pre-eclampsia.…”
Section: Selenium In Reproductive Health 266mentioning
confidence: 99%
“…Vitamins C and E. After contradictory pilot trial findings [287][288][289], vitamins C and E do not decrease preeclampsia risk; rather, they are more frequently associated with birthweight <2.5 kg and adverse perinatal outcomes [290][291][292][293]. There is insufficient evidence to make a recommendation about the usefulness of the following: new severe dietary salt restriction for women with any HDP, ongoing salt restriction among women with pre-existing hypertension, heart-healthy diet, and calorie restriction for obese women (all III-L; all Very low/Weak).…”
Section: Preventing Preeclampsia and Its Complications In Women At Inmentioning
confidence: 99%